PERBANDINGAN TEKNIK ORTHOREKTIFIKASI CITRA SATELIT SPOT5 WILAYAH SEMARANG DENGAN METODE DIGITAL MONO PLOTTING (DMP) DAN METODE RATIONAL POLYNOMIAL COEFFICIENTS (RPCs) - Atriyon Julzarika (Indonesian National Institute of Aeronautics and Space (LAPAN), 2009)
Quality of accuracy and precision is the main problem in survey and mapping. One of the problems in remote sensing is the geometrical correction using the orthorectification of the satellite imagery. Conceptually, it is the same with the orthorectification of oblique air photos. This research study is about how to orthorectify the SPOT5 imagery of Semarang using DMP and RPCs methods. SPOT5 satellite can acquire data with a sensor angle up to 200, so it produces oblique images. This DMP method use the Colinear equation with the condition of Polynomial order 2 (horizontal) and the height value was obtained from Digita Terrain Model (DTM). RPCs methods use parameters of interior orientation of its metadata and are also assissted by eight ground control points from DTM. Adjustment computation is used to compute the differential orthoimage model to produce new parameter values that will be used for orthorectification. This result of orthorectification is tested by overlaying toward the Indonesian Topography Map (RBI) scale 1:25.000 and the ground survey. Keywords: SPOT5, Orthorectification, DMP, RPCs